Skin temperature change in patients with meibomian gland dysfunction following intense pulsed light treatment - Yun, Jeongseop; Min, Ji Sang (Frontiers in Medicine, 2022)
Purpose: This study aimed to determine whether superficial telangiectatic vessel ablation occurs during intense pulsed light (IPL) treatment in patients with meibomian gland dysfunction (MGD) by measuring the patients’ skin temperature. Methods: The medical records of 90 patients (90 eyes) with MGD who underwent IPL treatment were analyzed. The patients underwent IPL treatment four times every four weeks. Ocular surface disease index (OSDI) scores and dry eye (DE) and MGD parameters were obtained before the first IPL treatment and after the fourth IPL treatment. The skin temperatures of the upper and lower lids were obtained before every IPL treatment. Results: The skin temperature of the upper and lower lids gradually decreased with every IPL treatment. The decrease in skin temperature was statistically significant. OSDI scores and DE and MGD parameters improved after the fourth IPL treatment. Conclusion: Results showed that superficial telangiectatic vessels were indirectly reduced by the decrease in skin temperature during IPL treatment in patients with MGD.